Simple and rapid colorimetric detection of melanoma circulating tumor cells using bifunctional magnetic nanoparticles. Issue 24 (15th November 2017) - Li, Junrong; Wang, Jing; Wang, Yuling; Trau, Matt
Abstract : The rapid and sensitive detection of melanoma circulating tumor cells was achieved utilizing the nanozyme activity and separation property of magnetic nanoparticles. Abstract : Circulating tumor cells (CTCs) are a promising biomarker for monitoring cancer metastasis and therapy response. However, the rarity and inherent fragility of CTCs pose great challenges for CTC detection. Currently, CTC detection requires advanced instruments that might be inaccessible in most hospitals or labs. To allow simple and rapid CTC detection, we propose a sensor platform that relies only on the intrinsic properties of magnetic nanoparticles (MNPs) including rapid separation as well as nanozyme activity. The detection of melanoma CTC, which causes most skin cancer-related deaths, is demonstrated based on bifunctional MNPs. The magnetic property of MNPs enables melanoma CTC isolation and enrichment within 5 min from blood. The nanozyme activity of MNPs allows naked-eye detection of melanoma CTC by catalyzing the oxidation of colourless 3, 3′, 5, 5′-tetramethylbenzidine (TMB) into blue coloured products. Melanoma CTC enumeration can be further achieved by UV-vis measurement. Our platform has successfully detected 13 melanoma CTCs per mL within 50 min. We thus believe this platform could find broad applications both in the clinic and in research.